Os Objetivos do Desenvolvimento Sustentável nos planos diretores municipais: uma análise das capitais brasileiras - Almeida, Bruna Wandscheer de (2023)
As a member of the United Nations and a signatory to the 2030 Agenda and the Sustainable Development Goals (SDGs), Brazil is committed to implementing actions aimed at sustainability. The implementation of these instruments demands an active role from public management, requiring integrated urban planning, with viable and efficient strategies that enable municipalities to apply them. Thus, master plans, developed as a basic guide for urban development policy, become tools for implementing these guidelines. Based on this, the objective of this research is to evaluate how the SDGs are being covered in master plans in different areas of the country, by selecting and analyzing Brazilian capitals, enabling discussion on initiatives and recommendations for their best implementation. The research used the following methodological steps: (i) identification of goals that fit the local context and that can be guided by municipal planning; (ii) survey of the local scope of each goal with a set of keywords for searching in the plans; and (iii) search for the set of words in each master plan using the Nvivo software, resulting in a table and graphs with the percentages of incidence of each goal in the master plans. As a result, the master plans of Fortaleza and São Paulo stood out from the others, covering at least one goal of each SDG. SDG 11 presented the highest coverage rate of guidelines in the plans, followed by SDG 12 and SDG 6. In addition, SDGs 7, 8 and 9 were relevant, covering most of the plans analyzed, although to a lesser extent. This research reflects on the role of cities in the implementation of the 2030 Agenda and the SDGs, showing how municipal legislation can be directed towards meeting these goals. In addition, it offers suggestions for good practices that can be replicated in other municipalities, contributing to a more efficient implementation of the SDGs in Brazil.